2023
DOI: 10.7717/peerj.15781
|View full text |Cite
|
Sign up to set email alerts
|

Thalattosuchian crocodylomorphs from European Russia, and new insights into metriorhynchid tooth serration evolution and their palaeolatitudinal distribution

Abstract: From the Middle Jurassic to the Early Cretaceous, metriorhynchid crocodylomorphs inhabited marine ecosystems across the European archipelago. Unfortunately, European metriorhynchids are only well known from Germany, France, and the UK, with the Eastern European fossil record being especially poor. This hinders our understanding of metriorhynchid biodiversity across these continuous seaways, and our ability to investigate provincialism. Here we describe eleven isolated tooth crowns and six vertebrae referable t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 92 publications
0
9
0
Order By: Relevance
“…Among metriorhynchids, Young et al [40] reported several indeterminate metryorhynchid teeth, cf. Thalattosuchus, and two morphotypes of Geosaurini indet.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Among metriorhynchids, Young et al [40] reported several indeterminate metryorhynchid teeth, cf. Thalattosuchus, and two morphotypes of Geosaurini indet.…”
Section: Discussionmentioning
confidence: 99%
“…Thalattosuchus and Tyrannoneustes sp. [40], all of which have no marked differences from their contemporary congeners of Western Europe. This is not surprising, as the invertebrate faunas of the middle and late Callovian are also highly similar in these basins [91,144].…”
Section: Figure 22mentioning
confidence: 95%
See 3 more Smart Citations